Extensive hybridization and past introgression between divergent lineages in a quasi‐clonal hermaphroditic fish: Ramifications for species concepts and taxonomy. (19th April 2020) - Tatarenkov, Andrey; Earley, Ryan L.; Taylor, D. Scott; Davis, William P.; Avise, John C.
Abstract: Extreme inbreeding is expected to reduce the incidence of hybridization, serving as a prezygotic barrier. Mangrove rivulus is a small killifish that reproduces predominantly by self‐fertilization, producing highly homozygous lines throughout its geographic range. The Bahamas and Caribbean are inhabited by two highly diverged phylogeographic lineages of mangrove rivulus, Kryptolebias marmoratus and a 'Central clade' closely related to K. hermaphroditus from Brazil. The two lineages are largely allopatric, but recently were found in syntopy on San Salvador, Bahamas, where a single hybrid was reported. To better characterize the degree of hybridization and the possibility of secondary introgression, here we conducted a detailed genetic analysis of the contact zone on San Salvador. Two mixed populations were identified, one of which contained sexually mature hybrids. The distribution of heterozygosity at diagnostic microsatellite loci in hybrids showed that one of these hybrids was an immediate offspring from the K. marmoratus x Central clade cross, whereas the remaining five hybrids were products of reproduction by self‐fertilization for 1–3 generations following the initial cross. Two hybrids had mitochondrial haplotypes of K. marmoratus and the remaining four hybrids had a haplotype of the Central clade, indicating that crosses go in both directions. In hybrids, alleles of parental lineages were represented in equal proportions suggesting lack of recent backcrossing to either of the parental lineages. However, sympatric populations of two lineages were less diverged than allopatric populations, consistent with introgression. Results are discussed in terms of applicability of the biological species concept for isogenic, effectively clonal, organisms. Abstract : Extreme inbreeding is expected to reduce the incidence of hybridization, serving as a prezygotic barrier. Here we report hybridization between two highly diverged, predominantly self‐fertilizing lineages of mangrove rivulus, K. marmoratus and a "Central clade". Crosses go in both directions and hybrids reproduce by self‐fertilization.